2015
DOI: 10.1186/s12967-015-0695-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cytokine autoantibodies in postherpetic neuralgia

Abstract: BackgroundThe mechanisms by which varicella zoster virus (VZV) reactivation causes postherpetic neuralgia (PHN), a debilitating chronic pain condition, have not been fully elucidated. Based on previous studies identifying a causative role for anti-cytokine autoantibodies in patients with opportunistic infections, we explored this possibility in PHN.MethodsSera from herpes zoster (HZ) patients without and with PHN (N = 115 and 83, respectively) were examined for the presence of autoantibodies against multiple c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
0
27
0
3
Order By: Relevance
“…For example, 2 patients with herpes zoster/postherpetic neuralgia (HZ/PHN) had high IL-6 transcription levels in affected skin [27]. In another study, 6 patients with herpes zoster had anti-IL-6 antibodies [28]. In a third study, elevated levels of IL-6 protein were found in the cerebrospinal fluid of patients with central nervous system disease secondary to VZV vasculopathy [29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, 2 patients with herpes zoster/postherpetic neuralgia (HZ/PHN) had high IL-6 transcription levels in affected skin [27]. In another study, 6 patients with herpes zoster had anti-IL-6 antibodies [28]. In a third study, elevated levels of IL-6 protein were found in the cerebrospinal fluid of patients with central nervous system disease secondary to VZV vasculopathy [29].…”
Section: Discussionmentioning
confidence: 99%
“…Using an established in vitro assay [20,25,29,37,44,45], the neutralizing capacity of specific anti-interferon autoantibodies, were evaluated using control peripheral blood mononuclear cells (PBMC). In these experiments, PBMC were incubated in the presence of 10% healthy volunteer or patient sera and left unstimulated or stimulated with the cytokine recognized by the specific anticytokine autoantibody found in the serum samples.…”
Section: Analysis Of Anticytokine Autoantibody Neutralization Activitymentioning
confidence: 99%
“…This is because LIPS is a fluidphase immunoassay that presents autoantigens such as cytokines in solution, allowing them to adopt native structures. Numerous studies have shown LIPS to generate highly informative anticytokine autoantibody profiles in multiple human disorders [20,25,28,30,[37][38][39][40]. In one study, LIPS was shown to strongly track the anticytokine autoantibodies observed by ELISA and protein array, but LIPS demonstrated autoantibody levels spanning a larger dynamic range of detection [30].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical neurophysiology and the techniques used to study the trigeminal functions remain convenient diagnostic and research tools to document clinically evident lesions or to uncover subclinical abnormalities. Certain impaired fibers may initiate chronic pain states after the development of subsequent localized nerve lesions due to VZV infection . Blink reflexes, which are mediated by nonnociceptive myelinated A‐beta fibers, and trigeminal laser‐evoked potentials, which are mediated by nociceptive myelinated A‐delta and unmyelinated C fibers, have been used to evaluate afferent pathways of V1 in patients with PHN .…”
mentioning
confidence: 99%
“…Certain impaired fibers may initiate chronic pain states after the development of subsequent localized nerve lesions due to VZV infection. [9][10][11] Blink reflexes, which are mediated by nonnociceptive myelinated A-beta fibers, 12,13 and trigeminal laserevoked potentials, which are mediated by nociceptive myelinated A-delta and unmyelinated C fibers, 14,15 have been used to evaluate afferent pathways of V1 in patients with PHN. 16 Sensory nerve conduction (SNC) studies enable the direct measurement of sensory nerve action potentials (SNAPs), amplitudes and sensory conduction velocities (SCVs), thus providing quantitative measures of the functions of large fibers in the nerve.…”
mentioning
confidence: 99%